The dark side of trust: When trust becomes a 'poisoned chalice'. (March 2014) - Skinner, Denise; Dietz, Graham; Weibel, Antoinette
Trust is typically portrayed as beneficial to all concerned; something which is inherently good. In this article we focus on interpersonal trust and argue that, while there are undoubted benefits, trust can also be problematic; there are circumstances in which it can become a 'poisoned chalice' for one or other of the parties involved. We question whether the potential for negative experiences in relation to trust has been fully explored and argue that its true dark side lies within the dynamics of the trust relationship. From this stance we use the social exchange and gift giving literatures to re-appraise trust in a way that highlights the importance of expectation and intent and demonstrates the circumstances in which trust may not be beneficial for one of the parties involved. We conclude with a research agenda which we believe will further develop our understanding of this complex human interaction.